Efektifitas Atraktan dalam Mengendalikan Lalat Buah (Bactrocera sp.) pada Tanaman Cabai Merah (Capsicum annuum L.) - Algifani, Farid; Damar Adelia, Anggun; Herdinawati, Herdinawati; Br Bangun, Loviga; Purba, Nurcahaya; Amalia Rahmadani1, Shinta; Arsi, Arsi (Seminar Nasional Lahan Suboptimal, 2021)
Algifani F, Adelia AD, Herdinawati H, Bangun LB, Purba N, Rahmadani SA, Arsi A.  2021. The effectiveness of attractants in controlling fruit flies (Bactrocera sp.) on chilli pepper (Capsicum annuum L). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 578-586.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Chili pepper (Capsicum annuum L.) was one of the important plants in Indonesia and had high economic value. The existence of chili plants cannot be separated from pests such as fruitflies (Bactrocera sp.). This study aimed to determine the effectiveness of anthrax compounds in controlling fruitflies attacks on chili plants. Symptoms of the attack caused by the presence of black spots on the chili. The methodology used in writing this paper was based on some literatures studied of scientific articles. The results of reviews from several journals, an anthraxant compound that was effective for controlling fruitflies pests on chili plants is methyl eugenol. The most effective dose of Methyl Eugenol was 1.5 ml/trap. Utilization of used pheromones greatly affects the population of male fruit flies. This could significantly suppress and control the subsequent regeneration of fruitflies populations. The most effectively time to application Methyl Eugenol fruit fly trap was in the morning and evening. The most common fruitflies found in traps was the species Bactrocera dorsalis. In conclusion, pheromone traps are effective traps to reduce fruitflies populations on chili plants.